(untitled) (Communications in Computational Chemistry, 2025)
Iron-sulfur ([FeS]) clusters are among the most ancient and functionally diverse cofactors in biology, mediating processes ranging from electron transfer to substrate activation and catalysis. Within this broad class, non-cubane [FeS] clusters exhibit outstanding structural flexibility and chemical versatility. This review summarizes recent computational advances in elucidating the mechanisms of non-cubane [FeS] cluster-dependent enzymes, focusing on systems containing [2Fe–2S] and distorted [4Fe–4S] clusters. Representative enzymes discussed include biotin synthase (BioB), Rieske dioxygenases (NDO, BphA, NBDO), heterodisulfide reductase (Hdr), and carbon monoxide dehydrogenases (CODHs), that perform diverse chemical transformations such as sulfur insertion, aromatic cis-dihydroxylation, S–S bond cleavage, and CO₂/CO interconversion. Special emphasis is placed on how quantum chemical cluster modelling and QM/MM simulations have provided insights into transient intermediates, rate-determining steps, and the roles of metal nuclearity and heterometal incorporation in tuning catalytic reactivity.